Capitu no cinema: do roteiro ao texto fílmico - Benedito, Renata Batista (2012)
The literature and cinema, although they have different languages, because while it uses iconic language that makes use of a verbal language, both have a characteristic that is the possibility of narrating a fictional plot. This characteristic is the one responsible for the relationship between these two arts. This strong relationship in the process of adaptation of an art to another. Thinking about it, this dissertation is a study on the adaptation of the novel Dom Casmurro, Machado de Assis to the cinema. For both were chosen to compose the corpus of this research the film Capitu, Paul Cezar Saraceni and the screenplay of the same name written by Lygia Fagundes Telles and Paulo Emilio Salles Gomes. Our goal is to analyze how was the implementation of the narrative from one language to another, observing the treatment given to the novel's structural narrative elements in this process of adaptation. Noting how every artistic expression provides the categories: plot, character and focalization as well as the interpretation generated for each work. In order to support our research we rely on some theoretical and critical literature and cinema. In the analysis of narrative aspects used for both arts, authors of literary theory as the Russian formalist Tomachevski (1976), Genette (s / d), Antonio Candido (2007), Todorov (2008) and criticism related to Dom Casmurro. In relation to the cinema in order to clarify issues regarding the adaptation of theoretical reflections used as Robert Stam (2003), Brian McFarlane (1996), Ismail Xavier (1996; 2003) and João Batista de Brito (1995; 2006; 2007). We conclude that the way events are reordered and presented to us viewers, both the film and the script changed the construction of characters and their relationship with the episodes of the book.